Szemben a maffiával: avagy olajozott viszonyok - Kármán, Irén (Hungary : DordonyFilm, 2007)
An investigative look at the dubious petrol businesses involving high officials after 1989 in Hungray.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films